Radio frequency and coaxial cable assemblies. Detail specification for semi-rigid cable assemblies. Frequency range up to 6 000 MHz, type 50-12 low loss semi-rigid coaxial cable Part 4-3, (31st August 2022) - British Standards Institution,
No abstract available